In Pursuit of Authenticity in Science Education - Jens Anker-Hansen; Maria Andreé (Nordina: Nordic Studies in Science Education, 2019)
This article presents a systematic review of how authenticity is used in science education research and discusses the implications these uses have for the design of science education classroom practices. Authenticity has been discussed in education for decades. However, the authenticity of science education not only concerns the design of educational activities, but also the content of what is being taught. This article reviews research articles published in 2013 and 2014, in the three highest ranking journals in science education, regarding how authenticity is framed in science education. The findings suggest that the uses vary greatly from referring to externally defined practices to student relevance. The findings are discussed with the notions of cultural and personal authenticity to suggest important aspects involved with designing science classroom activities authentic to the different references. Based on the review, we have developed a strategy for balancing authenticity in science education classroom practices between cultural and personal authenticity.